The Role of Aquaculture in Human Life - Husniddin og‘li, Ahadov Akobir (American Journal of Botany and Bioengineering, 2026)
This study comprehensively analyzes the role and importance of aquaculture in human life. During the research, the contribution of aquaculture to ensuring food security, strengthening public health, socio-economic development, and maintaining ecological stability was studied. Based on the analysis of scientific literature and available statistical data, it was determined that aquaculture is of great importance as a source of high-quality and nutritious food, reducing the pressure on natural fish resources. The results of the study indicate the need for a scientifically based approach and the introduction of modern technologies for the sustainable development of aquaculture.